2018
DOI: 10.1371/journal.pone.0204030
|View full text |Cite
|
Sign up to set email alerts
|

Association between age at onset of independent walking and objectively measured sedentary behavior is mediated by moderate-to-vigorous physical activity in primary school children

Abstract: ObjectiveAge at onset of walking has been shown as an early predictor of physical activity in infants and children. However, little is known about whether age at onset of walking may predict sedentary behavior (SB). The aim of the present study was to examine the association between the timing of onset of walking and objectively measured SB, and whether this association is mediated by moderate-to-vigorous physical activity (MVPA) in children.MethodsThe subjects were 388 elementary school children aged 6–12 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…The mean time spent in sedentary leisure activities was 2.34 ± 1.08 h by girls and 2.48 ± 1.23 h by boys, being found significant differences between sexes only when time spent using PCs, tablets or game stations was analyzed, being higher the time dedicated by boys to this kind of activity (p < 0.001). Other studies showed this higher time spent by boys in recreational use of computers or other electronic devices [40], even though girls usually spent more time in sedentary behaviors [41].…”
Section: Discussionmentioning
confidence: 82%
“…The mean time spent in sedentary leisure activities was 2.34 ± 1.08 h by girls and 2.48 ± 1.23 h by boys, being found significant differences between sexes only when time spent using PCs, tablets or game stations was analyzed, being higher the time dedicated by boys to this kind of activity (p < 0.001). Other studies showed this higher time spent by boys in recreational use of computers or other electronic devices [40], even though girls usually spent more time in sedentary behaviors [41].…”
Section: Discussionmentioning
confidence: 82%
“…For example, in a recent study of 34‐year‐old Finnish twins, earlier learning to stand unaided in infancy was associated with higher self‐reported leisure‐time PA (LTPA) in young adulthood, 13 whereas limited evidence was found between ages at reaching infant motor milestones and self‐reported LTPA in adulthood in the study of 1946 British birth cohort 14 . Only two studies had examined the association between motor development and accelerometer‐measured ST, and both were conducted in childhood, and the sample sizes were relatively small 15,16 . Both these studies found association between later motor development and higher ST in childhood.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, on improving the physical preparation of children to fulfil physical standards, in particular, the «Ready for Work and for the Defense» complex, the authors prove that for those who go in for physical culture it is necessary to organize a training process taking into account individually differentiated trajectories (Osipov et al, 2016;Tanaka et al, 2018). Experts prove that for each physical quality, an individual training of different functional intensity for adolescents of different physical levels and individual weekly physical activity should be compiled (Aoyama et al, 2018;Yarmak et al, 2018). This study proves that it is the differentiation of groups in school by body mass index that has a significant positive effect on physical development, in particular on improving the endurance and dexterity of schoolchildren.…”
Section: Discussionmentioning
confidence: 99%
“…According to experts, it is only through increasing the physical and health-improving knowledge of schoolchildren that it is possible for them to form a set of values in the field of a healthy lifestyle and full social adaptation (Donnelly et al, 2009;Magdalena et al, 2016). The implementation of this process based on the didactic possibilities of using individually differentiated technologies will increase its efficiency by improving the indicators of physical qualities, increasing the level of functional capabilities of schoolchildren and motivating adolescents to physical activity (Aoyama et al, 2018;Cvetković et al, 2018).…”
Section: Introductionmentioning
confidence: 99%